EVALUASI KETAHANAN GALUR HARAPAN KEDELAI TERHADAP PECAH POLONG DAN KERAGAAN KARAKTER AGRONOMI YANG SESUAI UNTUK IKLIM TROPIS - Krisnawati, Ayda; Adie, M. Muchlish (Perhimpunan Biologi Indonesia, 2019)
ABSTRACT Pod shattering is one of major constraints in soybean cultivation at tropical environment. The objective of the study was to evaluate resistance to pod shattering and agronomic performance of several adapted to tropical environment. A total of 14 promising lines and two check cultivars (Anjasmoro and Dega 1) were evaluated in two locations (Mojokerto and Jembrana) on Februari to May 2018. The experiment design was a randomized block in each location, with 16 treatments and four replications. At R8 stage, 30 pods were randomly detached from five sample plants of each line to be used for evaluation of pod shattering resistance using oven dry method. Five promising lines from Mojokerto showed resistant to pod shattering, meanwhile three very resistant and two resistant lines were obtained from Jembrana. Those all resistant promising lines were the progenies of shatter-resistant parent (Anjasmoro). The pod shattering resistance was determined by the pod length, the longer the pods will increase sensitivity to shattering. However, the sensitivity of long pods can be minimized when width of the pod is narrow. The promising lines with shorter pod and the width of the pod is narrow, then this line has the chance to be resistant to pod shattering. The agronomic characters of soybean are suitable to be developed in tropical regions such as Indonesia are: maturity under 85 days, seed weight more than 14 g/100 seeds, medium plant height, and produce high number of pods. Based on the results of the study obtained one promising line which resistance to pod shattering, produce high productivity and have good agronomic characters. The lines is G511H/Anj//Anj///Anj////Anj-4 with production yield 3.43 t/ha and also adaptable to the tropics. Keywords: pod shattering, agronomic character, tropical soybean, path analysis